Between Fantasy And Finitude: Re-Appraising Kierkegaard’s Philosophy Of Despair With A Contemporary Existential-Psychotherapeutic Attitude Of (De)Spero (Existential Analysis: Journal of the Society for Existential Analysis, 2018)
This paper makes the case for the use of fantasy in exploring feelings of despair (contra Kierkegaard). I suggest that we adopt an existential-psychotherapeutic attitude towards the actuality of our (de)spero (despair/hope) and through the experience of balancing (de)spero, find liberation from, and peace within, our despair.
Keywords: Kierkegaard; despair; finitude; infinitude; (de)spero